Cytotoxic gold(I) complexes with amidophosphine ligands containing thiophene moieties - Goitia Semeco, Helen Rosmary (2019)
A new phosphine ligand bearing a thiophene moiety, C 4 H 3 SNHCOCH 2 CH 2 PPh 2 (L), has been prepared by reaction of the aminophosphine Ph 2 PCH 2 CH 2 NH 2 with thiophenecarbonylchloride in the presence of triethylamine. The coordination behavior towards gold(I), gold(III) and silver(I) species has been studied and several metal compounds of different stoichiometry have been achieved, such as [AuL 2 ]OTf, [AuXL] (X = Cl, C 6 F 5 ), [Au(C 6 F 5 ) 3 L], [AgL 2 ]OTf or [Ag(OTf)L]. Additionally, the reactivity of the chloride gold(I) species with biologically relevant thiolates was explored, thus obtaining the neutral thiolate compounds [AuL(SR)] (SR = 2-thiocitosine, 2-thiolpyridine, 2-thiouracil, 2-thionicotinic acid, 2,3,4,6-tetra-6-acetyl-1-thiol-β-D-glucopyranosato or thiopurine). The antitumor activity of the compounds was measured by the MTT method in several cancer cells and the complexes exhibit excellent cytotoxic activity.